The Eligibility of a Bankrupt to Receive Zakāh in Malaysia - Zameli, Mohamad Hisyam; Awang Hamat, Mohd Afandi (IIUM Press, 2021)
Bankruptcy is one of the worst conditions that individuals may face. Islamic law has informed the rules of the debt and warned against leniency in payment of debt and urged its payment, and has prescribed several methods for its payment, including the share of al-Ghārimīn. The jurists have set the parameters and conditions for the entitlement of al-Ghārimīn for zakāh. But the question remains about the issue of entitlement of a bankrupt to receive zakāh because there is no discussion on it in the books of jurisprudence. Therefore, this research intends to clarify the eligibility of a bankrupt to receive zakāh, especially from the al-Ghārimīn category. This research also intends to discover the ways in which the insolvency administration in Malaysia issues decisions on bankruptcy, and to search for the conditions for zakāh eligibility in Lembaga Zakat Selangor (LZS). Through the inductive approach, the researchers collected information related to the subject, and then they worked on analyzing the information and data obtained. The researchers concluded a number of results, the most important of which are: al-Ghārimūn are Muslim debtors and deserve zakāh to pay off their debts; the reasons for bankruptcy are among the most important factors for the eligibility of zakāh; and if the bankrupt has a deferred debt, it makes him ineligible to receive zakāh.